Risk-based quality assurance in private higher education: a design-based model - Muhammad Ridha Habibi Z; Restu Restu; Wildansyah Lubis (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2026)
Private higher education institutions require risk management systems that are not merely administrative but integrated with internal quality assurance. This study developed and evaluated a Design-Based Research (DBR) model that integrates risk management, the Internal Quality Assurance System (SPMI), the Internal Supervisory Unit (SPI), the PPEPP cycle, and the Indonesian National Standards for Higher Education (SN-Dikti). The study was conducted in one Indonesian private higher education institution through problem analysis, theoretically informed design, two iterative refinement cycles, and reflection. Data were collected through observation, interviews, document analysis, expert validation, implementability and practicality instruments, user reflection, and a pretest-posttest competence test involving 18 participants. The model was judged highly feasible by experts, implementable (M = 3.65/4), and practical (M = 3.50/4). Participant competence increased from 58.00 to 87.76, with a mean gain of 29.76 points, 95% CI [28.92, 30.60], p < .001, and N-Gain = .71. The model offers tentative design principles for risk-based quality assurance in resource-constrained private higher education.